RANCANG BANGUN ROLE BASED ACCESS CONTROL (RBAC) PADA SISTEM DONASI BERBASIS WEB UNTUK PANTI ASUHAN - dzaki diana; Dzaki Mutammadien Illiyin; Moh. Aminollah Hamzah; Anwari; Fathorrozi Ariyanto (LPPM Universitas Abdurrab, 2026)
The rapid advancement of information technology has driven digital transformation across various sectors of life, including donation management in non-profit institutions such as orphanages. At Al-Muthi Orphanage, recording practices still rely on manual Microsoft Excel, leaving significant gaps in data security and accountability, primarily due to the absence of access restrictions between users. This research aims to develop and implement an online donation platform by adopting the Role Based Access Control (RBAC) framework, which regulates access rights into three user categories: Admin, Caregiver, and Donor. The Waterfall method was chosen as the development approach, covering system requirements analysis, design using UML and ERD, coding utilizing PHP Native and MySQL, as well as testing phases. The resulting platform presents various innovations including horizontal RBAC (access restrictions between users with equal authority), layered verification mechanisms for financial transactions, state-based lock system (data locking after verification with privileged access for Admin), account lifetime, proportional transparency, donation schemes without login requirements, public activity galleries, and password recovery facilities. Based on test results, the system successfully achieved all targets for vertical RBAC (100%), horizontal RBAC (100%), state-based lock system (100%), account lifetime (100%), and donor privacy protection (100%), while cross-check verification reached 80%. The usability assessment using the SUS method yielded a score of 81.00 classified as the Excellent category, and donor trust level reached 4.3 out of 5, or Very High. Overall, the integration of RBAC into the donation information system has proven effective in strengthening data security and donation management accountability at Al-Muthi Orphanage.